2021
DOI: 10.3390/pathogens10111491
|View full text |Cite
|
Sign up to set email alerts
|

Informing Stewardship Measures in Canadian Food Animal Species through Integrated Reporting of Antimicrobial Use and Antimicrobial Resistance Surveillance Data—Part II, Application

Abstract: Using the methodology developed for integrated analysis and reporting of antimicrobial use (AMU) and antimicrobial resistance (AMR) data, farm-level surveillance data were synthesized and integrated to assess trends and explore potential AMU and AMR associations. Data from broiler chicken flocks (n = 656), grower–finisher pig herds (n = 462) and turkey flocks (n = 339) surveyed by the Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS) at the farm-level (2015–2019) were used. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Step 2 was implemented at the end of 2018 and eliminated the preventive use of aminoglycosides, macrolides, penicillins, and streptogramins. Between 2019 and 2020, the incorporation of the Step 3 strategy ended the preventive use of bacitracin and tetracyclines [ 14 , 26 ]. It is important to note that the strategy does not include the prohibition of the use of these antimicrobials for treatment of disease under veterinary supervision in the face of an outbreak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2 was implemented at the end of 2018 and eliminated the preventive use of aminoglycosides, macrolides, penicillins, and streptogramins. Between 2019 and 2020, the incorporation of the Step 3 strategy ended the preventive use of bacitracin and tetracyclines [ 14 , 26 ]. It is important to note that the strategy does not include the prohibition of the use of these antimicrobials for treatment of disease under veterinary supervision in the face of an outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies in Canada characterized AMR in indicator and foodborne bacteria from turkey flocks and retail turkey meats and found antimicrobial-resistant bacteria and AMR phenotypes that have potential food safety implications [20][21][22]. Similarly, other turkeyproducing countries have reported high levels of multidrug resistance (MDR) (resistance to �3 antimicrobial classes) in E. coli isolates and resistance to WHO's Highest Priority Critically Important Antimicrobials (HP-CIA) including beta-lactams, 3 rd , and 4 th generation cephalosporins, aminopenicillins, fluoroquinolones and polymyxins (colistin) [23][24][25][26][27]. Studies have also shown that the use of antimicrobials in turkey flocks was significantly associated with the development of resistance to the same or unrelated antimicrobials [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…CIPARS has advanced its farm-level analysis by developing the defined daily dose in animals using Canadian standards (DDDvetCA) [ 10 , 44 ]. Dose-based indicators were applied to the CIPARS Farm AMU Surveillance data for characterizing AMU trends between species and investigated for their utility for studying AMU–AMR linkages [ 45 ]. Additionally, the dose-based indicators were used for monitoring the impact of the changes in voluntary and regulatory AMU practices (i.e., from disease prevention to disease treatment or disease control, progressive elimination of certain classes of antimicrobials) [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dose-based indicators were applied to the CIPARS Farm AMU Surveillance data for characterizing AMU trends between species and investigated for their utility for studying AMU–AMR linkages [ 45 ]. Additionally, the dose-based indicators were used for monitoring the impact of the changes in voluntary and regulatory AMU practices (i.e., from disease prevention to disease treatment or disease control, progressive elimination of certain classes of antimicrobials) [ 45 , 46 ]. Other sectors intending to develop their capacity for AMU surveillance could progressively improve their data collection and analytic capacity to enable the reporting of indicators relevant to their sector.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings may have been impacted by criteria of this review that were shaped by the needs of the larger iAM.AMR project at this stage of model development, such as the pragmatic exclusion of continuous factors. The use of continuous quantitative AMU indicators in surveillance reporting provides additional granularity for understanding the impact of AMU (compared to categorical binary measurements), and the reporting of such indicators is becoming more common [ 31 , 58 ]. The research team plans to incorporate continuous quantitative AMU indicators, in particular, into future iterations of the iAM.AMR project's model structure.…”
Section: Discussionmentioning
confidence: 99%